Enhance of TiO2 dopants incorporated reduced graphene oxide via RF magnetron sputtering for efficient dye-sensitised solar cells - Low, Foo Wah; Lai, Chin Wei; Lee, Kian Mun; Juan, Joon Ching (Springer Verlag, 2018)
In particular, the dye-sensitised solar cells (DSSCs) have a high potential in the rational energy conversion efficiency to secure our sustainable energy source. In the present study, advanced radio frequency (RF) magnetron sputtering technique was applied to incorporate titanium dioxide (TiO2) dopants into reduced graphene oxide (rGO) nanosheet for improving the power conversion efficiency (PCE) of DSSCs device. An optimum TiO2 content incorporated onto rGO nanosheet plays an important role in improving the PCE of DSSCs by minimising the recombination losses of photo-induced charge carriers. Based on the results obtained, 40-s sputtering duration for incorporating TiO2 dopants onto rGO nanosheet exhibits a maximum PCE of 8.78% than that of pure rGO film (0.68%). In fact, the presence of optimum content of TiO2 dopants within rGO nanosheet could act as mediators for efficient separation photo-induced charge carriers. However, the excessive of sputtering duration (e.g. 60 s) of TiO2 dopants onto rGO nanosheet results higher charge recombination and lowers the PCE of DSSCs (5.39%).